Maternal Cigarette, Alcohol, and Coffee Consumption in Relation to Risk of Clubfoot. Issue 1 (24th November 2014) - Werler, Martha M.; Yazdy, Mahsa M.; Kasser, James R.; Mahan, Susan T.; Meyer, Robert E.; Anderka, Marlene; Druschel, Charlotte M.; Mitchell, Allen A.
Abstract Background Clubfoot is associated with maternal cigarette smoking in several studies, but it is not clear if this association is confined to women who smoke throughout the at‐risk period. Maternal alcohol and coffee drinking have not been well studied in relation to clubfoot. Methods The present study used data from a population‐based case–control study of clubfoot conducted in Massachusetts, New York, and North Carolina from 2007 to 2011. Mothers of 646 isolated clubfoot cases and 2037 controls were interviewed about pregnancy events and exposures, including the timing and frequency of cigarette smoking, alcohol intake, and coffee drinking. Results More mothers of cases than controls reported smoking during early pregnancy (28.9% vs. 19.1%). Of women who smoked when they became pregnant, those who quit in the month after a first missed period had a 40% increase in clubfoot risk and those who continued to smoke during the next 3 months had more than a doubling in risk, after controlling for demographic factors, parity, obesity, and specific medication exposures. Adjusted odds ratios for women who drank >3 servings of alcohol or coffee per day throughout early pregnancy were 2.38 and 1.77, respectively, but the numbers of exposed women were small and odds ratios were unstable. Conclusions Clubfoot risk appears to be increased for offspring of women who smoke cigarettes, particularly those who continue smoking after pregnancy is recognisable, regardless of amount. For alcohol and coffee drinkers, suggested increased risks were only observed in higher levels of intake.